2012
DOI: 10.1080/13691058.2012.708944
|View full text |Cite
|
Sign up to set email alerts
|

Parents' constructions of the sexual self-presentation and sexual conduct of adolescents: discourses of gendering and protecting

Abstract: In this article, we explore the discourses on sexuality that a sample of parents drew upon when they talked about teenage sexual self-presentation and conduct. The sample consisted of 43 parents (32 mothers and 11 fathers) of adolescents and pre-adolescents; data were gathered using in-depth interviews and were analysed using a strategy known as modified analytical induction. Findings indicated that while an acceptance the traditional heterosexual script permeated participants' accounts, and protective discour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Some parents have no theoretical or historical basis for their argumentation because, during their adolescence, the topic was also neglected by their parents. (1,5,11) In the present study, fathers showed greater facility for discussing this topic with male children, a fact corroborated by other authors, who found that addressing sexuality with male children was easier. (11,14) In this respect, boys are less inhibited and therefore start their sexual lives earlier than girls.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Some parents have no theoretical or historical basis for their argumentation because, during their adolescence, the topic was also neglected by their parents. (1,5,11) In the present study, fathers showed greater facility for discussing this topic with male children, a fact corroborated by other authors, who found that addressing sexuality with male children was easier. (11,14) In this respect, boys are less inhibited and therefore start their sexual lives earlier than girls.…”
Section: Discussionsupporting
confidence: 79%
“…This authoritarian approach has cultural reflections because, historically, the approach to sexuality by the family has been restricted to preventing pregnancy. (11) Concerns about how to behave in the face of a child's demonstration of sexuality are still raised by parents. The parents understand sexuality as something related to reproduction, which directly implies pregnancy and sexually transmitted diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while the account in factor 2 places sex in a casual and fun setting, the third discourse highlights a struggle between a relational ideal and an reality defined by lack of control around sexual activity. This factor supports research that highlights the potential problems that can emerge when more prohibitive societies portray especially young girls' sexuality as something that is dangerous and needs to be controlled, instead of highlighting the right of young people to experience sexual pleasure freedom as more sexually open societies seem to do (Joshi, Peter, and Valkenburg 2011;Hyde et al 2012). It seems that these mixed messages are taken up by young people themselves.…”
Section: Discussionsupporting
confidence: 59%
“…Discourse 1, for example, the most common of the narratives produced by the young people in the study tells a story of responsibility, intimacy and sensitivity. Within the context of existing research as well as dominant societal and media portrayals of young men (Joshi, Peter and Valkenburg 2011;Hyde et al 2012), the number of young men who drew on this factor is surprising. In this it supports research by Smiler (2008, 17) who identified relational reasons for young men's dating and sexual engagement and challenges researchers to go "beyond stereotypes when examining boys' romantic and sexual relationships".…”
Section: Discussionmentioning
confidence: 99%